Analysis of strain accumulation of the faulting zones by the help of continuous GPS stations - Arslan, Asude. (Thesis (M.S.)-Bogazici University. Kandilli Observatory and Earthquake Research Institute, 2007., 2007)
The NOlih Anatolian Fault Zone (NAFZ) belongs to one of the largest recent active fault systems in the Earth and it is the most effective zone in the Anatolian Plate. During the last decades a westward expansion of large earthquakes along the North Anatolian Fault has extented till the Sea of Marmara. The researchers give attention to the seismic gap in the Mmmara Sea. It is expected that northem and middle strand of NAFZ have a strong risk for future actions. The purpose of this study has two main goals. First one is to estimate velocity field of the region, and the second one is to investigate changes of the strain accumulation in the region by seven continuous GPS stations. This investigation is done by tiangulation method and by using GPS coordinate differences obtained from 2002 to 2004 periods. Strain parameters such as maximum and minimum principal strains, direction of the maximum and principal strain, maximum shear strain parameters and its direction are detennined.
Keywords: Faults (Geology) -- Turkey.; Strains and stresses.; Global Positioning System.